The relationship between job satisfaction and organizational commitment among non-academic staff at Institut Pendidikan Guru Kampus Darulaman / Radiyatul Haslina Kamaruddin - Kamaruddin, Radiyatul Haslina (2014)
The purpose of this study was to investigate the relationship between job satisfaction and organizational commitment among non-academic staff in Institut Pendidikan Guru Kampus Darulaman. Jitra, Kedah. The study also differences in demographic factors on satisfaction work and commitment to the organization. In addition, this research looked at dimension satisfaction with the relationship and influence on organizational commitment among. A total of 66 respondents participated in this study. Data were analyzed using the software Statistical Package for Social Science (SPSS) version 15.0. There are two types of statistics used descriptive statistics and Pearson Correlation Coefficient. Descriptive statistic is used to analyze the demographic profile: meanwhile correlation coefficient was conducted to analyze relationship between the independent variable and dependent variable. The study carried out revealed that there were significant correlations between the three dimensions of job satisfaction and organizational commitment. The dimensions of job satisfaction are job itself, supervision, promotion. While the three dimension for organizational commitment are the affective organizational commitment, normative organizational commitment and continuance organizational commitment. The analysis also shows that there is a relationship between job satisfaction and organizational commitment. A study the future may be made on factors other variables using more respondents in Malaysia.